Effects of national directorate of employment on youth poverty status in Southwestern Nigeria (2017)
Youth unemployment is one of the most serious socio-economic problems currently confronting Nigeria. Its effect is felt on the high rate of poverty among the youth. The National Directorate of Employment (NDE) was an initiative, which targeted skills development and job creation among the youth. However, few studies exist on its impact on youth poverty. Therefore, effects of NDE on youth poverty status in Southwestern Nigeria were investigated. A two-stage sampling procedure was used to select respondents for the study. Out of the six Southwestern states, Osun, Oyo and Ogun were randomly selected. Simple random sampling was used to select 244 NDE participants of five years and above, with 155 non-NDE participants selected using snowball technique to give a total sample size of 399 respondents. Data were analysed using descriptive and inferential statistics. The findings revealed that majority of the respondents were male with mean age of 31.0±6.1 years. Half of the respondents (50.4%) were married, earning a mean income of N21,831.7 monthly. About 57.0% participated in agricultural training and 85.2% exhibited high knowledge of NDE activities. The greatest challenge faced by 66.0% of participants was insufficient fund (1.6±0.7), with the most important benefit derived being technical skills (1.09±0.71). More participants (27.1%) were better off than non-participants (21.3%) in poverty status. Furthermore, no significant difference (t=1.95; p>0.05) exists in poverty status of participants and non-participants. However, there was a significant difference (t=15.08; p<0.00) in the poverty status of participants in agricultural and nonagricultural training. The NDE activities had a low impact on the poverty status of participants. There should be an upward review of both monetary and material grants given to the participants to create a positive effect on the poverty status of participants,